SOCIAL DISTANCING POLICY AS A MEANS OF IMPROVING PUBLIC AWARENESS DURING COVID-19 PANDEMIC: A LITERATURE REVIEW - Oktaviani, Ulfa; Andriani, Helen (UI Scholars Hub, 2022)
To reduce COVID-19 transmission during the epidemic, most countries implemented a social distancing policy. However, without the people's compliance, this implementation will be useless. The combination of individual and environmental variables is critical to the success of initiating and maintaining health behaviors. The purpose of this study is to assess public participation toward obedience social distancing policy as a means of improving public awareness during COVID-19 pandemic. A literature review was used in this research. PubMed, Google Scholar, and ProQuest, with a cut-off date of 29 June 2021, were used to do an electronic search with no language constraints. There were ten included studies. Several research looked at the impact of combining social distancing strategies with other interventions such as school closure, reduced contact with the community, antiviral treatment and prophylaxis, and immunization. This study proves that social distancing has a good effect if the general public implements it well. More research is needed to determine the factors that influence the efficacy of social distancing strategies. In order for the community to comply with social distancing policies during the epidemic, the government must also be more aggressive in pursuing policy violators.